A novel design of distributed oscillator based on the balanced oscillator technique - Nipapon Siripon (2018)
This paper presents the new structure of the distributed oscillator. Based on the balanced oscillator concept, the new oscillator provides the two identical output signals using the extra transmission line. This oscillator is implemented on FR4. Then the output signals are investigated. According to the experimental results, the oscillator provides the free-running oscillating signal of 1.8 GHz. The magnitude and phase of the two outputs are tested. It is found that the signal of one output is lower than the combined output by approximately 3 dB. Furthermore, the injection-locked oscillator technique is employed to stabilize the oscillating signals and decrease the phase noise. In the locking state, it is found that the signal from the output of the Wilkinson divider is higher than the signal from one oscillator's output by about 3dB. This can also be confirmed the properties of the distributed oscillator's outputs. © 2013 IEEE.